Effectiveness of Cloth Face Masks to Prevent Viral Spread: A Comprehensive Review - Maryam Abdullah Alsaadoun et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Cloth face masks have been widely used as a public health intervention to reduce the spread of respiratory viruses, particularly during the COVID-19 pandemic. While medical-grade masks are known for their efficacy, cloth masks have gained attention due to their accessibility, affordability, and ease of production. This review evaluates the effectiveness of cloth masks in preventing viral transmission, focusing on their filtration efficiency, wearability, and public compliance. The limitations of cloth masks, such as inconsistent performance and inadequate fit, are discussed alongside strategies to improve their protective potential. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/294 DOI: https://doi.org/10.5281/zenodo.14559970